Impact of surrounding environments and vegetation on wind comfort assessment of a new tower with vertical green park. (January 2022) - Ricci, A.; Guasco, M.; Caboni, F.; Orlanno, M.; Giachetta, A.; Repetto, M.P.
Abstract: Modern architectural concept of "vertical forest" boosts the tendency of including permeable and green spaces in buildings and its surroundings. However, whilst green spaces generally make buildings and cities more ecofriendly, it is insufficiently known to which extent the surrounding environment and the vegetation may positively or negatively influence the pedestrian-level wind comfort quality of buildings amidst historical and well-settled urban layouts. This was the scope of the present study for which wind-tunnel (WT) testing and 3D RANS simulations were performed on two facing towers in Medellìn (Colombia), in order to ( i ) investigate the wind field and the pedestrian-level wind comfort around the towers; ( ii ) to compare the performance of WT and 3D RANS for wind comfort analysis; ( iii ) to evaluate the impact of the environment surrounding the two towers and ( iv ) the mitigation effects of vegetation on wind comfort. WT tests were performed on a scaled model (1:250) without surrounding, for 12 wind directions and 3 sets of measurement positions. The same case study without (i.e. CFDs) and with (i.e. CFDd) surrounding environment was simulated by 3D RANS. Next, an implemented CFDd case including vegetation (i.e., CFDd-V) was simulated for three LAD values. Overall, the surrounding had a significant impact on wind comfort assessment. The CFDd case showed a better-quality class than WT and CFDs. The CFDs and WT case showed a satisfactory agreement and the similar comfort quality class. The vegetation provided a remarkable improvement of comfort quality class mainly for set 1 and 2 . Graphical abstract: Image 1 Highlights: A newly designed tower with vertical green park and permeable spaces is presented. Pedestrian-level wind comfort with/without environment and vegetation is analyzed. Wind-tunnel tests and RANS simulations are used for predicting the wind flow field. The surrounding environment plays a key role in pedestrian-level wind comfort study. Vegetation can improve the comfort in permeable spaces highly exposed to winds.